Differences in glycolytic metabolism between tissue-resident alveolar macrophages and recruited lung macrophages - Woods, Parker S.; Mutlu, Gökhan M. (Frontiers in Immunology, 2025)
Immunometabolism has emerged as a key area of focus in immunology and has the potential to lead to new treatments for immune-related diseases. It is well-established that glycolytic metabolism is essential for adaptation to hypoxia and for macrophage inflammatory function. Macrophages have been shown to upregulate their glycolytic metabolism in response to pathogens and pathogen-associated molecular patterns such as LPS. As a direct link to the external environment, the lungs’ distinctive nutrient composition and multiple macrophage subtypes provide a unique opportunity to study macrophage metabolism. This review aims to highlight how the steady-state airway and severely inflamed airway offer divergent environments for macrophage glycolytic metabolism. We describe the differences in glycolytic metabolism between tissue-resident alveolar macrophages, and other lung macrophages at steady-state and during inflammation/injury. We also provide an overview of experimental guidelines on how to assess metabolism at the cellular level using Seahorse-based bioenergetic analysis including a review of pharmacologic agents used to inhibit or activate glycolysis.